مفهوم الذات لدى المراهق المتمدرس المكتئب وغيرالمكتئب - خليفي, جهينة; رضواني, مريم (University of Eloued جامعة الوادي, 2021)
الملخص: هدفت الدراسة الحالية الى معرفة مستوى مفهوم الذات لدى المراهق المتمدرس لتلاميذ السنة الرابعة متوسط.ومستوى الاكتئاب لدى المراهق المتمدرس، ومعرفة اذا ما كان هناك فروق في مستوى مفهوم الذات من افراد العينة المكتئبين والغير مكتئبين. ولقد بلغت عينة الدراسة (108) تلميذا وتلميذة، من تلاميذ الرابعة متوسط موزعين على متوسطتين متوسطة الخوارزمي ومتوسطة عبد الرحمان الناقص بالبياضة، ولتحقيق أهداف الدراسة استخدمت الطالبتان المنهج الوصفي الاستكشافي والادوات التالية: -مقياس مفهوم الذات من اعداد صلاح ابو ناهية (1990). -مقياس بيك للاكتئاب. وقد تم الاعتماد على برنامج الحزمة الاحصائية للعلوم الاجتماعية -التكرارات والنسب المئوية. - المتوسطات الحسابية والانحراف المعياري. -اختبار ك2 اللابارامتري. - اختبار Tللفروق بين عينتين مستقلتين. ومن أهم النتائج المتوصل اليها: -مستوى مفهوم الذات لدى المراهقين المتمدرسين منخفض. -مستوى الاكتئاب لدى المراهقين المتمدرسين مرتفع. -لا توجد فروق ذات دالة احصائية بين المكتئبين العاديين. -لا توجد فروق ذات دالة احصائية بين الذكور والاناث من المراهقين المتمدرسين. من مقياس مفهوم الذات - لا توجد فروق ذات دالة احصائية بين الذكور والاناث في مقياس الاكتئاب Résumé :انجلزية The current study aimed to know the level of self-concept of the adolescent schooled for fourth-year average students and the level of depression among the average adolescent and to find out if there are differences in the level of self-concept of depressed and non-depressed sample members . The sample of the study amounted to 108 male and female students from the fourth graders, distributed on two middle schools , Al-Khwarizmi middle school and Abdel Rahman Nagues in Al-Bayada, and to achieve the objectives of the study, the two students used the exploratory descriptive approach and the following tools: -Self-concept scale prepared by Salah Abu Nahia ( 1990) -Beck Depression Scale Thestatistical package for the social sciences program has been relied upon and among the statistical methods used Frequencies and percentages Arithmetic mean and standard deviation T-test for differences between two independent samples Ca2 laparametric test Among the most important results obtained The level of self-concept of the educated adolescent is low High level of depression in educated adolescents There are no statistically significant differences between depressed and non-depressed people There are no statistically significant differences between males and females of schooled adolescents between males and females in the level of self-concept.
دراسة وصفية استكشافية على عينة من تلاميذ الرابعة متوسط ببلدية البياضة بالوادي
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: ماهية الذات، الإكتئاب; La nature de soi, la dépression; The nature of the self, depression